Electron-beam chemistry in graphene - Effect of environmental SEM parameters on patterning and defect engineering. (January 2023) - Selhorst, Ryan; Susner, Michael A.; Muzzio, Ryan; Kao, I-Hsuan; Carpena-Núñez, Jennifer; Islam, Ahmad E.; Katoch, Jyoti; Maruyama, Benji; Rao, Rahul
Abstract: The engineering of defects in low-dimensional materials can enable the modulation of their optical, electrical, thermal, and structural properties. We have previously shown the ability to engineer precision patterned defects in graphene by electron beam irradiation in a controlled water vapor ambient within an environmental scanning electron microscope (ESEM). However, the relationship between instrumental parameters and structural changes in graphene are unexplored. Here, we investigate the relationships between parameters such as pressure, electron dose, and acceleration voltage on the electronic and structural properties of graphene as probed by Raman spectroscopy. There are dependencies on all of the studied parameters but electron dose is the dominant parameter that shows the most intense levels of structural modulation. Interestingly, control of instrumental parameters allows for the precision tailoring of features such as resolution (as determined by the beamskirting effect), doping, and functionalization – all of which make this process powerful for precision tuning of 2D materials and adds an enhanced technique for the development of next-generation electronics. Highlights: Graphene can be patterned in an SEM in the presence of water vapor. Pattern resolution can be as low as 60 nm, graphene is functionalized. Highest pattern resolution is achieved with the lowest pressure and dwell times. Electron dose affects strain and doping in the graphene.